The Drosophila Toll Pathway in Innate Immunity: from the Core Pathway toward Effector Functions. - Valanne, S.; Vesala, L.; Maasdorp, M.K.; Salminen, T.S.; Rämet, M. (Journal of Immunology, 2022)
The fruit fly Drosophila melanogaster Toll signaling pathway has an evolutionarily conserved role in controlling immune responses. Whereas the microbial recognition mechanisms and the core signaling pathway leading to activation of the humoral immune response via the NF-?B transcription factors have been well established for many years, the mechanistic understanding of the effector functions at the molecular level is currently rapidly evolving. In this review, we discuss the current developments in elucidating the role of the Drosophila Toll signaling pathway in immunity. We discuss the emerging role of Toll in viral infections and sex-specific differences in immunity. Mainly, we focus on Toll pathway regulation, the effector molecules, and cellular immunity.